(3TQM eaJGM GdYdhe ddScGcis - (3bWH GdOjf GdTjQGRis; (3bWH GdOjf eMehO Hf eSYhO GdTjQGRj, bWH GdOjf GdTjQGRj,J (B710 (3g` s
(3ChdgG (B:s
n (3CQHGHgG hGdeYfi CfgG Ef UMJ s
(3BNQgG (B:s
(3Je HYhf Gddg hMSf Jhajbg s
(3GdYfhGf HcTa GdXfhf hGdGYdGe(B: (3eaJGM GdeaJGMs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B65s
Keywords: (3GdHdGZIs